Solid waste management in India: An assessment of resource recovery and environmental impact - Isher Judge Ahluwalia; Utkarsh Patel (Indian Council for Research on International Economic Relations (ICRIER), 2018)
This study analyses the environmental and financial sustainability of solid waste management in Indian cities. It presents an assessment of the rapidly rising volume of municipal solid waste, its changing composition, the continuing practice of mixing biodegradable (wet) waste with dry waste at the source of generation, and the growing volume of plastic in the waste. The present system is focussed on collection and transportation of largely mixed unsegregated waste. Resource recovery from the waste and safe disposal of the residual waste in scientifically designed landfills are grossly neglected. Rules have now been put in place for sustainable solid waste management, but the capacity to plan and manage the system and ensure the enforcement of the rules is a major challenge. The inability to ensure segregation of waste comes in the way of proper recycling, effective functioning of biomethanation plants, and also of safe operation of waste to energy plants which consequently leads to release of toxic pollutants into the atmosphere. Sites allocated for landfills are used as open dumping sites where far too much waste is dumped without resource recovery, generating leachate and methane gas. This study also presents the sources of greenhouse gas emissions from the solid waste sector. Besides presenting some mitigation choices to respond to the growing challenge, it also suggests mechanisms for ensuring that the system is financially sustainable.
Keywords: Q32; Q53; Q58; 330; Solid Waste Management; Greenhouse Gas Emissions from Solid Waste Sector; Sustainable Materials Management; Waste to Energy